2016
DOI: 10.1152/japplphysiol.00445.2016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pacing modality on noninvasive assessment of heart rate dependency of indices of large artery function

Abstract: Studies investigating the relationship between heart rate (HR) and arterial stiffness or wave reflections have commonly induced HR changes through in situ cardiac pacing. Although pacing produces consistent HR changes, hemodynamics can be different with different pacing modalities. Whether the differences affect the HR relationship with arterial stiffness or wave reflections is unknown. In the present study, 48 subjects [mean age, 78 ± 10 (SD), 9 women] with in situ cardiac pacemakers were paced at 60, 70, 80,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…Many previous studies have shown the interaction between HR, Ea, and arterial stiffness, both in animal models and in humans. 2129 These data are consistent with ours, suggesting that blood vessels can adapt to increased mechanic wall stress changing their structure, benefitting from ivabradine-induced HR reduction, with a final improvement of Ea and VAC. According to previous evidence, the effect might be predominantly on the arterial system and less on LV end-systolic elastance (Ees).…”
Section: Effect Of Ivabradine On Endothelial Functionsupporting
confidence: 88%
“…Many previous studies have shown the interaction between HR, Ea, and arterial stiffness, both in animal models and in humans. 2129 These data are consistent with ours, suggesting that blood vessels can adapt to increased mechanic wall stress changing their structure, benefitting from ivabradine-induced HR reduction, with a final improvement of Ea and VAC. According to previous evidence, the effect might be predominantly on the arterial system and less on LV end-systolic elastance (Ees).…”
Section: Effect Of Ivabradine On Endothelial Functionsupporting
confidence: 88%
“…Until the participant's HR remained over 40 bpm, the investigational drugs could exert their HR-lowering and other effects without any restriction by the pacemaker. e rationale of using the middle and high HR levels was to study drug effects in a situation where their pharmacological HR-lowering capacity had been nonpharmacologically eliminated by pacing, a relatively neutral method in hemodynamic terms, but the drugs' other effects, including HR-independent effects, on hemodynamics were preserved [16]. To our knowledge, elimination of BB-or ivabradine-induced HR reduction by pacing has only rarely been done earlier and for purposes different from ours [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…(iii) We did not take into account the effects of different types of pacing modalities to investigate effects of HR changes on PPGF. Previous studies found that atrial pacing (Ap), ventricular pacing (Vp) and sequential atrioventricular pacing (ApVp) have different impact on haemodynamic changes such as ejection duration and central pulse pressure, while no change for PWV and augmentation index [36]. Since the PPGF was also independently determined by PWV, it is suggested that changes in PPGF due to HR changes may not be so different between different types of pacing modalities.…”
Section: Discussionmentioning
confidence: 99%